What You Don't Know About Schools
X, 294 p.
Keywords: We live in an era where our view of school is reduced by a superficial public conversation. In this context, the complexity of the educational process and the debate over the purpose of schooling is lost. This book brings together leading scholars of education to analyze these issues and engage the public in different ways of looking at school.